2004
DOI: 10.1007/s10194-004-0077-6
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin injections for the treatment of frontal tension headache

Abstract: We performed a randomized, double-blind, placebo-controlled trial to determine the efficacy of botulinum toxin type A (BOTOX; Allergan) in treating frontal tension-type headache (TTH). A total of 40 patients attending a headache treatment center were randomized to receive 50 U botulinum toxin type A or saline, injected at 10 sites of the forehead. Frequency and severity of headaches before and after injection were compared. The intensity of headaches in the botulinum toxin type A group, but not the placebo gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…These effects have yet to be demonstrated in humans (15). BoNTA efficacy as prophylactic treatment of TTH has been assessed in several small controlled trials, but the evidence of a treatment effect has thus far been mixed or lacking (17, 23, 25, 27, 30, 38). The reasons for the lack of efficacy of BoNTA treatment of CTTH in this trial may be related to the injection protocol, the BoNTA dosage range, the patient population or ineffectiveness in this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects have yet to be demonstrated in humans (15). BoNTA efficacy as prophylactic treatment of TTH has been assessed in several small controlled trials, but the evidence of a treatment effect has thus far been mixed or lacking (17, 23, 25, 27, 30, 38). The reasons for the lack of efficacy of BoNTA treatment of CTTH in this trial may be related to the injection protocol, the BoNTA dosage range, the patient population or ineffectiveness in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…BoNTA modification of pain pathways may potentially inhibit the pain associated with headache disorders. The results of double‐blind, placebo‐controlled trials, open‐label trials and retrospective chart reviews show mixed evidence of efficacy that focal injections of BoNTA significantly reduce the frequency, severity and disability associated with migraine, TTH and other types of headaches (16–30). The varying results may be due to patient selection, the number of BoNTA treatments administered, the injection protocol employed or the dosage range used.…”
Section: Introductionmentioning
confidence: 99%
“…There have been conflicting results for treatment with the muscle relaxant tizanidine [61,67], whilst the NMDA‐antagonist memantine was not effective [68]. Botulinum toxin has been extensively studied [69–79]. It was concluded in a systematic review that botulinum toxin is likely to be ineffective or harmful for the treatment of chronic TTH [63].…”
Section: Prophylactic Drug Treatment Of Tthmentioning
confidence: 99%
“…48,54 Botulinum toxin has been extensively studied but a systematic review concluded that it is is likely to be ineffective or harmful for the treatment of chronic TTH. 50,[55][56][57][58][59][60][61][62][63][64][65]…”
Section: Miscellaneous Agentsmentioning
confidence: 99%